THE TAXONOMICAL SIGNIFICANT OF COMPUTERD PHYLOGENETIC ANALYSIS AND MORPHOLOGICAL DATA IN SOME SPECIES OF POLYGONACEAE - & et al., Al-Newani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This research dealt with study of cladistics taxonomy of  five  species related to the genus Rumex L. and Polygonum L. from family polygonaceae in Iraq by using Mesquite software V.2.75. This  research support strongly delimiting  the species P. aviculare L. and P. lapathifolia L.as suggested in floras publication while R. dentatus L. is setted in single group whereas R. vesicarius L. and R. conglomeratus Murray were included in the same group. Also, this study involved characteristics of shape, dimensions, color, and ornamentation of seeds and fruits as  the seed forms were ranging from lenticular to trigonous. In terms of size calculations,  the seeds of R. vesicarius  was recorded the higher range (4.0- 4.5) mm in length while, P. aviculare recorded the lowest  (1.5-1) mm in length. However, the shape was lenticular in P. lapathifolia and trigonous in the remaining species. Color of seeds and surface ornamentation is recognized. fruits shape is an important characters in identification of selected species as two groups are  distinguished: persistent tubercules tepals which are spine teeth in R. dentatus and tongue like shape in R. conglomeratus, the second group is persistent tepals which are papery in P. lapathifolia, biconvex in P. aviculare and cordate to winged as in R. vesicarius beside that, colors, dimensions and surface nature is also recorded.